Effect of winter cold duration on spring phenology of the orange tip butterfly, Anthocharis cardamines. Issue 23 (7th November 2015) - Stålhandske, Sandra; Lehmann, Philipp; Pruisscher, Peter; Leimar, Olof
Abstract: The effect of spring temperature on spring phenology is well understood in a wide range of taxa. However, studies on how winter conditions may affect spring phenology are underrepresented. Previous work on Anthocharis cardamines (orange tip butterfly) has shown population‐specific reaction norms of spring development in relation to spring temperature and a speeding up of post‐winter development with longer winter durations. In this experiment, we examined the effects of a greater and ecologically relevant range of winter durations on post‐winter pupal development of A. cardamines of two populations from the United Kingdom and two from Sweden. By analyzing pupal weight loss and metabolic rate, we were able to separate the overall post‐winter pupal development into diapause duration and post‐diapause development. We found differences in the duration of cold needed to break diapause among populations, with the southern UK population requiring a shorter duration than the other populations. We also found that the overall post‐winter pupal development time, following removal from winter cold, was negatively related to cold duration, through a combined effect of cold duration on diapause duration and on post‐diapause development time. Longer cold durations also lead to higher population synchrony in hatching. For current winter durations in the field, the A. cardamines population of southern UK could have a reduced development rate and lower synchrony in emergence because of short winters. With future climate change, this might become an issue also for other populations. Differences in winter conditions in the field among these four populations are large enough to have driven local adaptation of characteristics controlling spring phenology in response to winter duration. The observed phenology of these populations depends on a combination of winter and spring temperatures; thus, both must be taken into account for accurate predictions of phenology. Abstract : Variation in winter conditions has lead to local adaptation in spring phenology of four latitudinally separate populations of a butterfly. At current winter durations there are already noticeable effects on phenology, and with future climate change winter condition will have a bigger impact on observed phenology.